2012
DOI: 10.1038/ctg.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Colon Visualization During Colonoscopy of the Addition of Simethicone to Polyethylene Glycol-Electrolyte Solution: A Randomized Single-Blind Study

Abstract: OBJECTIVES:Colonic bubbles associated with polyethylene glycol-electrolyte solution (PEG-ELS) are common and obscure mucosal visualization. This study aimed to determine whether adding simethicone decreases the incidence of bubbles.METHODS:Prospective, single-blind, randomized comparison of split dose PEG-ELS vs. PEG-ELS+simethicone (PEG-S) for outpatient colonoscopy. Bubble severity for colonic segments was assessed on withdrawal as A=no/minimal bubbles, B=moderate bubbles/interfere with detecting 5 mm polyp,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…To detect an ADR increased to 27.9% with 80% power using a cut‐off for statistical significance of 0.05 would require a sample size of at least 1412 patients, and obviously, there was no single trial that met this criterion. Additionally, according to the forest plot, it is obvious that, excepting the two RCTs conducted by Matro et al . and de Leone et al ., the other four trials reported numerically higher ADRs during colonoscopy in the SIM group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…To detect an ADR increased to 27.9% with 80% power using a cut‐off for statistical significance of 0.05 would require a sample size of at least 1412 patients, and obviously, there was no single trial that met this criterion. Additionally, according to the forest plot, it is obvious that, excepting the two RCTs conducted by Matro et al . and de Leone et al ., the other four trials reported numerically higher ADRs during colonoscopy in the SIM group.…”
Section: Discussionmentioning
confidence: 93%
“…In order to improve the level of bowel cleansing, simethicone (SIM), a kind of oral antifoaming agent, has been added to several PEG‐based bowel preparation regimens, for it reduces bubbles in bowel segments so as to improve visualization of the colonic mucosa and promote emission of excessive gas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search strategy identified 535 potentially relevant records after excluding duplicates. After careful review, 36 studies that met inclusion criteria were further evaluated for eligibility, and 12 full‐text articles from 2009 to 2017 were included in this meta‐analysis . The review process is illustrated by a flowchart of Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Simethicone, an anti‐foaming agent, has long been used to eliminate bubbles by being added to the irrigation water or being an adjunct of bowel preparation regimens . One meta‐analysis showed that oral simethicone helps reduce bubbles and improves visibility in upper gastrointestinal endoscopy, but the ADR was not evaluated because few studies had addressed this issue at the time it was published.…”
Section: Introductionmentioning
confidence: 99%